Morphological and Anatomical Characteristics of Moroccan Fir Needles in Talassemtane National Park, North-Western Rif Region, Morocco - Hajar Lamrhari; Mariem Ben-Said; Zineb Jalal; Dhar El Mehraz; Hassan Bouziane (European Scientific Journal, ESJ, 2020)
Moroccan fir, Abies maroccana Trab. forms a unique forest community in the Mediterranean basin and has a great ecological and biological values in Moroccan Rif Mountains. However, morphological and anatomical characters of the needles are poorly investigated for A. maroccana. This research examined the morphological and anatomical characters of Moroccan fir needles in order to determine the phenotypic needles traits of Abies maroccana. The study was carried out in the National Park of Talassemtane, Western Rif, Morocco. Data was collected from two-year-old needles in six stands. In each site, seven trees were selected, and 60 needles were collected from each tree. Five morphological and one anatomical characters of the needles were examined. The variance analysis (ANOVA) of quantitative needles variables revealed significant inter-tree morphological variability of needles of A. maroccana. Based on the morphological characters studied, the multivariate analysis (PCA) separated all trees of Moroccan fir into four groups: (A) long, thin and large; (B) long, thin and narrow; (C) short, large and thick; and finally (D) short and thick needles. As demonstrated here, the fir needles were mainly characterized by: 2 types of apex (obtuse–acute and acute needles), a broad base and the marginal resin canals. This diversity can be attributed to genetic variation and / or influence of ecological conditions.